Establishment and application of a structure evolution model for aqueous foam based on fractal theory. Issue 7 (13th January 2017) - Wang, Fei; Li, Zhaomin; Chen, Hailong; Zhang, Xibin
Abstract : A new model based on fractal theory is proposed for the simulation of aqueous foam. It reveals that the evolution trend of the fractal dimension of foam is non-linear with the changing of time following an exponential equation. Abstract : The evaluation and simulation of foam-based materials are still matters of significant debate, despite the large number of available studies, due to the excellent properties of foam and its successful applications, especially in oil and gas field development. The properties of foam are substantially determined as a result of a dynamic structure, however few studies have been reported which investigate and perform measurements related to such a structure. In this work, a new model based on fractal theory is proposed for the simulation of aqueous foam. As a first step, the fractal characteristics of foam are confirmed using image processing and calculations. Accordingly, the foam structure is quantitatively studied by defining and calculating the foam fractal dimensions. Secondly, a foam structure evolution model is established, which reveals that the evolutional trend of the fractal dimensions of foam is non-linear with the changing of time, following an exponential equation. The model is then validated and a sensitivity analysis is also carried out. Finally, the applications of this model to the evaluation of foaming agents and the prediction of foam structures are discussed. These results are expected to be helpful for further understanding the dynamic characteristics of foam fluids and their advanced applications.